176k views
6 votes
Find the formula for g(x) if it is known that g(x-3)=2x-6

User Cdwilson
by
5.4k points

2 Answers

6 votes
factor out variable g
g (x-3) = 2x-6

Divide both sides by 3.
g(x-3)/x-3 = 2x-6/x-3

g=2x-6/x-3
User MorrisIriga
by
5.0k points
13 votes

Answer:

g(x-3)=2(x-3)-6

Explanation:

just plug in x-3 wherever there is an x value in the original equation

User Biggdman
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.